The Euler characteristic of hypersurfaces in space forms and its application to isoparametric hypersurfaces - Albuquerque, Rui (2021)
We revisit the Allendoerfer–Weil formula for the Euler characteristic of embedded hypersurfaces in constant sectional curvature manifolds, taking time to re-prove it while demonstrating techniques of ([http://hdl.handle.net/10174/26893]) and then applying it to gain new understanding of isoparametric hypersurfaces.